Analysis on pedestrian infrastructure design at rail transit stations along Kelana Jaya line - Nik Othman, Nik Nurul Aziemah; Kadar Hamsa, Abdul Azeez; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor (Eastern Asia Society for Transportation Studies (EASTS), 2017)
Public transport is one of the components that help in reducing the traffic congestion and traffic accidents by providing mobility as well as accessibility to people. As there are increasing in the numbers of transit users, there are also increasing regarding demand for a better walking environment either from the station or to the station. In providing a better walking environment to the users, the pedestrian infrastructure should be continuously be monitored and improved to meet the user's demand. The purpose of this paper is to analyze the existing pedestrian infrastructure provided at each selected station and the issues that lead to the low usage of the infrastructure.